2011
DOI: 10.1007/s11418-011-0564-4
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic lipid ingredients from cashew nuts

Abstract: Five new phenolic lipids, 2-(8"Z-eicosenoyl)-6-(8'Z-pentadecenyl) salicylic acid (3), 2-(9"Z-hexadecenoyl)-6-(8'Z, 11'Z-pentadecadienyl) methyl salicylate (5), 2-(10"Z, 13"Z-nonadecadienoyl)-6-(8'Z, 11'Z-pentadecadienyl) salicylic acid (6), 2-(16"Z-pentacosenoyl)-6-(8'Z-pentadecenyl) salicylic acid (7) and 2-(9"Z-octadecenoyl)-6-(8'Z, 11'Z-pentadecadienyl) methyl salicylate (8), and three known compounds, cardols (1), anacardic acid (2) and cardanols (4), were isolated from the nuts of the cashew, Anacardium o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 15 publications
1
10
0
1
Order By: Relevance
“…Anacardic acid mixture was submitted to a chromatographic column impregnated with AgNO 3 and each individual component was isolated and characterized by NMR spectroscopy. Complete and unequivocal proton and carbon assignments were performed and corroborated by literature data [ 10 , 11 ].…”
Section: Resultssupporting
confidence: 54%
“…Anacardic acid mixture was submitted to a chromatographic column impregnated with AgNO 3 and each individual component was isolated and characterized by NMR spectroscopy. Complete and unequivocal proton and carbon assignments were performed and corroborated by literature data [ 10 , 11 ].…”
Section: Resultssupporting
confidence: 54%
“…In future studies, it will be interesting to analyze in vivo AA isotypes separately, since recent in vitro studies have shown different immunological properties on AAs compounds [57]. In our study, all administered doses of AAs were associated with increased antioxidant enzyme activity whereas only the 50 mg/kg dose of AAs reduced the increase in cytokine levels caused by DEP exposure.…”
Section: Discussionmentioning
confidence: 54%
“…In fact at the 150 and 250 mg/kg doses, a significant increase in the concentration of IL-1 β was observed. A possible reason for this is that the overall exposure to anacardic acid-4 is increased above a threshold in the highest concentrations, whereby it could enhance the production of cytokines as described by Suo et al [57] for IL-2, interferon- γ , IL-4, and IL-5.…”
Section: Discussionmentioning
confidence: 99%
“…Diets containing nutmeats, such as walnut, peanut, almond, hazelnut, pistachio, macadamia, cashew nut and Brazil nut, protect the heart, decrease chronic-disease mediators, such as gut fat, stabilize glycemic index, reduce resistance to insulin, and may also decrease the risk of diabetes and cancer (Papanastasopoulos & Stebbing, 2013). Anacardic acid is a phenolic compound present in cashews (Agostini-Costa et al, 2004;Correia, David, & David, 2006;Trevisan et al, 2006) that has been associated with a series of specific pharmacological activities, including anti-microbial, histone acetyltransferase inhibition, anti-cancer and anti-inflammatory (Kubo, Masuoka, Ha, & Tsujimoto, 2006;Stasiuk & Kozubek, 2010;Suo et al, 2012).…”
Section: Introductionmentioning
confidence: 99%